PENGARUH E-SERVICE QUALITY DAN ELECTRONIC WORD OF MOUTH (E-WOM) TERHADAP KEPUTUSAN PEMBELIAN PRODUK KOSMETIK EMINA (Studi Pada Remaja Di Kota Surabaya) - Nur Fitria Febriyanti; Renny Dwijayanti (Pusat Riset dan Inovasi Nasional, 2022)
Currently, local products are very developed and favored by teenagers, one of the product is cosmetic products. Cosmetic products are often used by Indonesian people, especially women in their daily life as their daily needs. There are various kinds of business people who sell cosmetic products, one of them is Emina who gives the advantages of the products offered. This study aims to determine the effect of E-Service Quality & Electronic Word Of Mouth on Emina Cosmetic Product Purchase Decisions in the Community of Surabaya City. This type of research is quantitative. The research population taken is people who live in Surabaya with the age of 12-25 years by taking samples using non-probability sampling methods, and getting a sample of 210 respondents. Data analysis is in the form of multiple linear regression analysis with the help of IBM SPSS version 22. The results of the study showed that the E-Service Quality (X1) & Electronic Word Of Mouth (X2) variables had an effect on the Purchase Decision (Y) variable either partially or simultaneously. The coefficient of determination shows that 2 independent variables contributed 54.9% and the remaining 45.1% was influenced by other variables.